1982
DOI: 10.1515/botm.1982.25.8.351
|View full text |Cite
|
Sign up to set email alerts
|

Sterol Distribution in Red Algae from the Waters of Eastern Long Island

Abstract: Seven species of red algae from the waters of eastern Long Island, New York were analyzed for their sterol content. The species studied were: Agardhiella tenera, Ahnfeltia plicata, Chondrus crispus, Corallina officinalis^Cystoclonium purpureum var. cirrhosum, Gracilaria foliifera, und Palmaria palmata. The major sterols found belong to C 27 compounds. Cholesterol was the predominant sterol in all species with the possible exception of Palmaria palmata. The presence of cholest-7-en-3/3-ol is reported for the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Thus, although in earlier studies sitosterol was cited as the major sterol in C. crispus (Heilbron, 1942;Saito and Idler, 1966), now it is know that the major sterol is cholesterol as was observed in this study (Alcaide et al, 1968(Alcaide et al, , 1969Freire and Ribas, 1975;Goldberg et al, 1982). Moreover, Iatrides et al (1978) cited cholesterol as the only sterol occurring in C. crispus.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Thus, although in earlier studies sitosterol was cited as the major sterol in C. crispus (Heilbron, 1942;Saito and Idler, 1966), now it is know that the major sterol is cholesterol as was observed in this study (Alcaide et al, 1968(Alcaide et al, , 1969Freire and Ribas, 1975;Goldberg et al, 1982). Moreover, Iatrides et al (1978) cited cholesterol as the only sterol occurring in C. crispus.…”
Section: Discussionmentioning
confidence: 45%
“…Fattorusso et al (1975) believed that desmos-terol seemed to have some taxonomic significance since it was found in some species of Gigartinaceae (Goldberg et al, 1982;Patterson, 1992). However, Goad and Goodwin (1972) observed that the proportion of cholesterol and desmosterol can vary from sample to sample in a given species, with some samples containing only cholesterol or both C 27 sterols.…”
Section: Discussionmentioning
confidence: 99%